Analysis of Adenomyosis Incidence based on Age and Neutrophil-lymphocyte Ratio Factors - Kurniati, Yuni Prastyo; Romadhon, Yusuf Alam; Parawansa, Karmila Indar Parawansa (JHeS (Journal of Health Studies), 2024)
Adenomyosis is a type of disorder which endometrial glands and stroma grow in the myometrium. This disease causes a very high burden of health care, which  82.0% of patients undergoing hysterectomy and 37.6% on chronic pain medication. There is research on the neutrophil-lymphocyte ratio (NLR) which is increased in this disease. However, there is still very limited research on this matter. Analytical observational research method with a cross sectional approach. A total of 135 samples using the consecutive sampling method. Data from Anatomical Pathology medical records from 2018 to 2023. Analysis using univariate, chi square test, and multivariate logistic regression. The results showed that the incidence of adenomyosis was highest in reproductive age (86.8%) and the NLR value at risk was 64.7%. The chi square test and logistic regression obtained the same findings, namely that there was a significant relationship between age and NLR on the incidence of adenomyosis (p<0.001). The prevalence ratio of age and NLR factors is 16.17 and 19.01. This means that NLR at risk has a 19.01 times on the incidence of adenomyosis, rather than age. Negelkerke R-square shows that age and NLR influence the incidence of adenomyosis by 54.9%. In conclusion, there is a significant relationship between the incidence of adenomyosis based on age and NLR. The implications of this study show that NLR can be a simple predictor for the incidence of adenomyosis. This can be done especially in women of reproductive age with a history of dysmenorrhea with complaints of chronic pain.